Informační systém pro filmový festival - Kupka, Stanisław (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Film je kulturní dílo, které se rychle stalo fenoménem 20. století. Filmové festivaly jsou pak oslavou celého spektra výtvorů a jejich autorů. Festivaly pomáhají přispívat k rozvoji filmového průmyslu a kinematografie. Snahu o zefektivnění organizování této společenské akce může podpořit zavedení informačního systému, který může pomoci dosáhnout větší návštěvnosti a spokojenosti diváků.

Film is cultural piece which has quickly become as phenomena of Twentieth Century. Film festivals are celebration of all spectrum of works and theirs authors. Festivals contributes to development of film industry and cinematography. Endeavor to improve organization's effectiveness of this social event can be done by establishing an information system which can help to reach higher attendance and satisfaction of visitors.
Information System for Film Festival
Keywords: Film; festival; informační systém; návštěvnost; organizace; financování; návštěvník; kino; informace; databáze; internet; registrace; vstupenka.; Film; festival; information system; attendance; organization; financing; visitor; cinema; information; database; internet; registration; ticket.